Development of epoxy/rice straw-based cellulose nanowhiskers composite smart coating immobilized with rare-earth doped aluminate: Photoluminescence and anticorrosion properties for sustainability. Issue 4 (15th February 2022) - Binyaseen, Adel M.; Bayazeed, Abrar; Al-nami, Samar Y.; Al-Ola, Khulood Abu; Alqarni, Sara A.; Abdel-Hafez, Shams H.; El-Metwaly, Nashwa M.
Abstract: Novel epoxy resin (E)/CNW nanocomposite coatings were developed with different total contents of rare-earth doped aluminate nanoparticles (REA NPs). The produced epoxy-cellulose nanowhiskers-rare earth doped aluminate nanoparticles (E-CNW-REA) coatings were applied onto mild steel. The epoxy/CNW nanocomposite coatings were characterized by X-ray fluorescence analysis (XRF), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDXA), transmission electron microscope (TEM) and infrared spectra (FT-IR). Both colorimetric properties and transparency of the nanocomposite coatings were proved by exploring UV–Vis absorption spectroscopy and CIE Lab parameters. The hardness and superhydrophobic properties were also explored. The photoluminescent transparent coatings showed an excitation at 365 nm, and a bright green emission wavelength at 517 nm under UV light. The corrosion protection performance of the coated mild steel samples soaked in an aqueous solution of sodium chloride (3.5%) was investigated using electrochemical impedance spectroscopy (EIS). The coatings with CNW were found to have anti-corrosion properties. Moreover, the nanocomposite coating with CNW (1 w%) was monitored to exhibit the most pronounced long-persistent photoluminescence for 60 min in the dark. The photoluminescent coatings exhibited highly durable long-lasting phosphorescence. Thus, the current strategy can be considered as a simple promising technology for industrial production of anti-corrosive, superhydrophobic and long-persistent phosphorescent.